Poly I:C elicits broader and stronger humoral and cellular responses to a Plasmodium vivax circumsporozoite protein malaria vaccine than Alhydrogel in mice - Costa-Gouvea, Tiffany B. L.; Françoso, Katia S.; Marques, Rodolfo F.; Gimenez, Alba Marina; Faria, Ana C. M.; Cariste, Leonardo M.; Dominguez, Mariana R.; Vasconcelos, José Ronnie C.; Nakaya, Helder I.; Silveira, Eduardo L. V.; Soares, Irene S. (Frontiers in Immunology, 2024)
Malaria remains a global health challenge, necessitating the development of effective vaccines. The RTS,S vaccination prevents Plasmodium falciparum (Pf) malaria but is ineffective against Plasmodium vivax (Pv) disease. Herein, we evaluated the murine immunogenicity of a recombinant PvCSP incorporating prevalent polymorphisms, adjuvanted with Alhydrogel or Poly I:C. Both formulations induced prolonged IgG responses, with IgG1 dominance by the Alhydrogel group and high titers of all IgG isotypes by the Poly I:C counterpart. Poly I:C-adjuvanted vaccination increased splenic plasma cells, terminally-differentiated memory cells (MBCs), and precursors relative to the Alhydrogel-combined immunization. Splenic B-cells from Poly I:C-vaccinated mice revealed an antibody-secreting cell- and MBC-differentiating gene expression profile. Biological processes such as antibody folding and secretion were highlighted by the Poly I:C-adjuvanted vaccination. These findings underscore the potential of Poly I:C to strengthen immune responses against Pv malaria.